العناقيد الصناعية كآلية للنهوض بقطاع التمور من أجل التنويع الإقتصادي في الجزائر - عنقود صناعة التمور بولاية بسكرة نموذجا - - خبيزة, انفال حدة; كرامة, مروة (جامعة الوادي - University of Eloued, 2023)
جاءت هذه الورقة البحثية من أجل تسليط الضوء على العناقيد الصناعية كآلية من أجل التنويع الإقتصادي في الجزائر. ومن أجل النهوض بقطاع التمور مع التركيز والتطرق إلى دراسة حالة عنقود صناعة التمور في ولاية بسكرة. حيث أن إعتماد الجزائر على قطاع المحروقات في ظل هشاشة القطاع الفلاحي و القطاع الصناعي وباقي القطاعات الأخرى، وهذا يجعل الإقتصاد الوطني اقتصاد تبعية . فالجزائر تعتبر واحدة من بين البلدان التي تعاني من عجز في جهازها الإنتاجي، على الرغم مـما تمتلكها لموارد طبيعية وبشرية تؤهلها لتحقيق تطور اقتصادي كبير، ومن بين هذه الموارد الطبيعية يحتل قطاع التمور الجزائري مكانة مهمة في العالم الناجمة عن جودة منتجات التمور ما تم تعزيزها بعنقود صناعة التمور الذي سوف يرفع من هذا القطاع. This research paper came in order to shed light on the industrial clusters as a mechanism for achieving economic diversification in Algeria in order to advance the dates sector by focusing and addressing the case study of the cluster of dates industry in the state of Biskra, especially since Algeria depends on the fuel sector and is characterized by the fragility of the agricultural sector, the industrial sector and the rest of the other sectors. Which made him suffer from economic dependency. Algeria is considered one of the countries that suffer from a deficit in its production apparatus, despite the fact that it possesses natural and human resources that qualify it to achieve great economic development, including the Algerian date sector as a natural resource, which gave Algeria an important position in the world as a result of the quality of date products, which led to its strengthening with an industry cluster. Dates that will be raised from this sector. The cluster of dates industry is an idea that is trying to be implemented in Biskra, so it must provide a suitable environment for it and be under the supervision of experts and must be supported in order to complete this project, which could be a strong and large cluster and one of the most important cluster experiences in Algeria due to the strong date market and its high quality
Industrial clusters as a mechanism for the advancement of the dates sector for economic diversification in Algeria -the cluster of dates industry in the state of Biskra as a model-
مقال
Keywords: التنويع الإقتصادي ; العناقيد الصناعية ; قطاع التمور ; عنقود صناعة التمور